LINGUISTIC DIVERSITY AND ECONOMIC DEVELOPMENT - Tursunova Ozodaxon To’raxon qizi; Tursunxo‘jayeva Moxigul Maxmud qizi (Ustozlar uchun, 2025)
Linguistic diversity plays a vital role in shaping the socio-economic fabric of nations. While it fosters creativity and innovation, it may also pose challenges to economic integration and development. This paper explores the multifaceted relationship between linguistic diversity and economic development, emphasizing the need for inclusive language policies, multilingual education, and social cohesion. By leveraging linguistic diversity as an asset, societies can achieve sustainable growth and global competitiveness. The article draws on empirical studies and real-world examples to provide a comprehensive understanding of this complex interplay.